Immediate Outcome of Vlbw And Elbw Babies in a Tertiary Care Center of Nepal - Acharya, N; Mishra, P; Shrestha, N; Gupta, V (Journal of Nepalgunj Medical College, 2015)
Background: Very Low Birth Weight (VLBW) infants weigh <1500 grams and Extremely Low Birth Weight (ELBW) infants weigh <1000 grams. They are predominantly premature but may also be associated with Intrauterine Growth Restriction (IUGR). The VLBW rate is an accurate predictor of infant mortality rate. Objective: The study was aimed to find out the hospital incidence of VLBW and ELBW babies and outcome of these babies, till they were discharged from the hospital/NICU. Methods: A descriptive study was conducted among 109 cases who weighed less than 1500 grams. The babies were evaluated for mortality and various morbidities till they were discharged from the hospital. Descriptive statistics was applied using SPSS 21.0 to show antenatal profile and immediate outcome. Results: Out of 109 cases, ELBW were 30.2% and VLBW were 69.8%. Among the ELBW babies, 30.3% survived and 75% in VLBW. The mortality rate in ELBW and VLBW babies were 69.7% and 25% respectively. Among the ELBW, common morbidities were NNJ (94%), Presumed NNS (87.8%), RDS (82.6%), Hypoglycemia (56.5%), Hypothermia (26%), Birth Asphyxia (15.1%). In the VLBW group, common morbidities were Presumed NNS (86.4%), NNJ (82%), RDS (46.5%), Hypoglycemia (30.2%). The mean duration of hospital stay was 8.6 days (SD ± 3.38). Conclusions: Common immediate morbidities were NNS, RDS, Hypothermia, Anemia, Shock, CHD, Birth Asphyxia and NEC. Well trained staff in the NICU and medical facilities like availability of Surfactant therapy, more number of mechanical ventilators could improve the survival of these babies in our setting. Journal of Nepalgunj Medical College Vol.12(1) 2014: 32-34